DIGITALISASI, ERA TANTANGAN MEDIA (Analisis Kritis Kesiapan Fakultas Dakwah Dan Komunikasi Menyongsong Era Digital) - Rustam Aji (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2016)
This is simply the best book that I have read on the aesthetics of new media. Other authors have often made exaggerated and superficial claims about the novelty of art and design in the new digital technologies. Manovich offers us instead a sober and yet always fresh and exciting analysis of the relationships between new media and their predecessors, especially cinema. As a practicing artist as well as a theorist and historian of media, Manovich can explain the continuities with the past. This sense of history enables him to argue convincingly for the qualities of new media that he believes are truly new.————————————————————————–Teknologi digital merupakan teknologi yang tidak lagi mengggunakan tenaga manusia atau manual. Sistem digital adalah perkembangan dari sistem analog. Digitalisasi cenderung pada sistem pengoperasian yang otomatis dengan format yang dapat dibaca oleh komputer. Perubahan sistem analog ke digital telah mengubah banyak hal dan mengancam eksistensi media cetak. Sebagian besar pelanggan media cetak telah beralih ke penggunaan teknologi on line yang lebih feksibel, bisa membaca informasi terbaru kapan saja dan dimana saja. Penyajian yang lebih hidup telah menarik pengiklan.